Does teaching-research conflict affect research performance? The role of research stress, engagement and job insecurity - Rui Feng; Junjie Wu; Yunhui Xie (Cogent Education)
This study examines the relationship between teaching-research conflict and research performance among university faculty members, as well as the mediating role of research stress and research engagement, and explores the moderating effect of job insecurity. Data were collected from a sample of 189 university faculty members in China. The results of structural equation modeling indicate that teaching-research conflict does not significantly influence research performance since the mediating mechanisms of research stress and research engagement counteract each other. Specifically, the indirect effect of teaching-research conflict on research performance through research stress is positive, while the indirect path through research engagement is negative. Furthermore, job insecurity is revealed as a moderator in the relationship between teaching-research conflict and research stress. Specifically, job insecurity weakens the positive effect of teaching-research conflict on research stress.